The use of “define it!” game in teaching descriptive speaking - Maulana Yusuf Aditya (Penerbit STKIP PGRI Bangkalan, 2020)
English is one the great of world language and language is a tool to communicate with other people. Teaching English can be done through dialogues, pictures, games, etc. This research was designed to know the use of “Define it!” game in teaching and the students’ problem of “Define it!” game. This research was qualitative, here the researcher observed the teaching speaking descriptive by using “Define it!” game. This research was conducted one meeting and use observation checklist and interview as the data collection and the subject of this research are the student of the second A grade in SMPN 1 Bangkalan. The finding showed that the used of “Define it!” game in teaching speaking descriptive were: 1) describe something based on card picture, 2) the other player must guess what. Based on the observation and interview the researcher found the students difficulty in teaching speaking descriptive by using “Define it!” game. The problems of the student were: vocabularies (difficult to explore the idea and unconfident, it was problem obstructing them in teaching speaking by using “Define it!” game therefore they were scared to be wrong and shy to speak up. In the conclusion of the research showed that the use of “Define it!” game in teaching speaking descriptive was able to raise the students motivation, students desire to study, interest, did not bored and enjoy in teaching and learning process. Based on the research the student must keep their confidence and the result the observation and interview also indicate a good finding of the students’ implementation and response toward the application “Define it!” game in teaching and learning process..